A Model Predictive Control Approach for Stochastic Networked Control Systems - Bernardini, D.; Donkers, M.C.F.; Bemporad, A.; Heemels, W.P.M.H. (IFAC Proceedings Volumes, 2010)
In this paper we present a stochastic model predictive control (SMPC) approach for networked control systems (NCSs) that are subject to time-varying sampling intervals and time-varying transmission delays. These network-induced uncertain parameters are assumed to be described by random processes, having a bounded support and an arbitrary continuous probability density function. Assuming that the controlled plant can be modeled as a linear system, we present a SMPC formulation based on scenario enumeration and quadratic programming that optimizes a stochastic performance index and provides closed-loop stability in the mean-square sense. Simulation results are shown to demonstrate the performance of the proposed approach.